Determine the Background Characteristics of Abattoir Butchers in Sishiagu, Tamale Metropolis - Asare, Solomon Ossom; Bulama, Ahmed Abdu; Udoh, Mary Athanasius; Tahidu, Issifu (Darul Yasin Al Sys, 2025)
This study aimed to determine the background characteristics of abattoir butchers in Sishiagu, Tamale Metropolis. A total of two hundred structured questionnaires were used to collect data on participants' background characteristics of abattoir butchers, and data analysis was performed using SPSS version 21. The results showed that all butchers (95.5%) in this study were male, while 4.5% with 20.7% aged less than 20yrs 43.7% between 20yrs and 30 yrs, 25.9% 31yrs to 40yrs, 7.4% 41yrs to 50yrs and 2.2% 51yrs to 60yrs, less than half (43.7%) of the butchers were older than 29yrs. Additionally, 61.9% of butchers were married, while 36.6% were single and Divorced was 1.5%. The study found that 46% had less than 10 years of work experience, while 24% had 11 to 20 years of experience. Notably, 20.7% of butchers were uneducated, with only 0.7% with postgraduate, 5.9% holding a university degree, 26.7% with SSS/SHS and 20.7% with JHS. Furthermore, tenure of years in the business was found to be 30.4% at the age of 1yrs to 5yrs, 35.6% at 6yrs to 10yrs and 34.1 % at 11yrs. There was a clear understanding that younger generation at the age of 20yrs to 40yrs is taking over the Abattoir Butchers. In conclusion, the study indicates that the work force in the abattoir are younger generation based on the background characteristics and as such a moderate awareness regarding meat hygiene among butchers and meat workers in Sishiagu, Tamale Metropolis should be obtainable.